2014
DOI: 10.1017/s095026881400257x
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of human infections with avian influenza A(H7N9) virus in the two waves before and after October 2013 in Zhejiang province, China

Abstract: We compared the epidemiological and clinical features of avian influenza A(H7N9) virus infections in the population in Zhejiang province, China, between March and April 2013 (first wave) and October 2013 and February 2014 (second wave). No statistical difference was found for age, sex, occupation, presence of underlying conditions, exposure history, white blood cell count, lymphocyte percentage and illness timeline and duration (all P > 0.05). The virus spread to 30 new counties compared to the first wave. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
22
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 14 publications
0
22
0
Order By: Relevance
“…This wave emerged in two principle locations, the Guangdong province of southern China and the Zhejiang province of eastern China [2,9,10]. The peak of the second wave coincided with the Chinese spring festival celebration of the lunar new year.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…This wave emerged in two principle locations, the Guangdong province of southern China and the Zhejiang province of eastern China [2,9,10]. The peak of the second wave coincided with the Chinese spring festival celebration of the lunar new year.…”
mentioning
confidence: 98%
“…The clinical and epidemiologic features of human H7N9 infection may have changed during this second wave. In addition to a geographic shift to southern China [2,9], the second H7N9 outbreak was associated with increased hospitalized patient fatality rates [10,11], including among individuals under 60 years of age [11]. Novel H7N9 variants were also detected in a number of cases in Guangdong, China [12][13][14].…”
mentioning
confidence: 99%
“…Disease symptoms, severity, and mortality generally have held constant between all three waves, and no pronounced antigenic drift has been detected from 2013 to 2015 (2). However, increased case-fatality rates re-ported in one province in China between cases from the first and second waves suggested that despite high homology between viruses isolated from different waves, it was possible that H7N9 viruses developed an enhanced ability to cause disease in humans (12). Previous studies with H7 subtype avian influenza viruses have demonstrated that even subtle changes can indicate enhanced adaptation to mammals, including increased transmissibility among mammalian hosts (6,(13)(14)(15), underscoring the need for ongoing surveillance and characterization of emerging H7N9 viruses as they continue to cause human infections.…”
mentioning
confidence: 99%
“…Finally, this cross-sectional study did not allow for examination of temporal or seasonal effects of inapparent avian exposure. It is generally known that a large number of live poultry is transported between rural poultry farms and wet markets in urban areas during the days of Chinese spring festival in January or February of each year17. This time period of festivities would be associated with increased exposure to infected poultry through direct or indirect (or inapparent) contact with avian influenza viruses.…”
Section: Discussionmentioning
confidence: 99%
“…The closures of LPMs appeared to decrease the risks of H7N9 infection in many Chinese cities such as Shanghai, Hangzhou, Huzhou and Nanjing15. However, the intervention was not always effective as demonstrated in Hangzhou and other counties of the Zhejiang province where new cases occurred after LPMs had been permanently closed in the winters of 2014 and 201516171819. The H7N9 virus continued to spread not only around LPMs, backyards, and small-scale poultry farms but also in natural environmental settings that were more difficult to detect20.…”
mentioning
confidence: 99%